ABOUT THE HISTORY OF COTTON FARMING IN UZBEKISTAN - H. O. Khushvaqtov (Galaxy International Interdisciplinary Research Journal, 2023)
The issues and problems of development of protected and gray lands in the field of agriculture in Uzbekistan in 1946-70 and the provision of these areas with qualified personnel are covered. There are also problems with the socio-economic and cultural life of the resettled people.